Ciric Type Theorem for Class of Contravariant Functions in Bi-polar Metric Space - Gandhi, Manjusha P.; Aserkar, Anushree A. (Communications in Mathematics and Applications, 2023)
In the current study, utilizing the Ciric type contraction condition, an attempt has been taken to prove new fixed point result for class of contravariant functions in bipolar metric space. The many previous results from the literature are extended, improved, and modified in this paper.
Keywords: Bi-polar; Bi-sequence; Bi-convergent; Fixed point